The Influence of CSR Programs on Financial Performance in the Banking Sector - Angraini, Anggella; Tyas, Hesti Ning; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
The basis of the study is the idea that corporate social responsibility, or CSR, suggests that doing this kind of activity will help the company by establishing its reputation and generating positive community feedback. The purpose of the study is to determine how a company's financial performance is impacted by its commitment to Corporate Social Responsibility (CSR). This report includes research conducted in China, India, Indonesia, and Pakistan. This research indicates that Corporate Social Responsibility (CSR) activities lead to continual performance improvement. Using a meta-analysis methodology, this study investigates the connection between financial success and corporate social responsibility (CSR). Based on theoretical assertions and real facts from the literature, ascertain whether there is a favorable association between financial performance and corporate social responsibility (CSR). If the research results are specified correctly, researchers find that although Corporate Social Responsibility (CSR) does not have much positive impact on short-term financial performance, Corporate Social Responsibility (CSR) offers extraordinary long-term fiscal benefits.